Transforming production technologies for more productivity and profitability towards doubling the farmers Income: success stories of large scale linseed cultivation at farmers field: Transforming production technologies for more productivity and profitability towards doubling the farmers Income: success stories of large scale linseed cultivation at farmers field - DEVENDRA K PAYASI (Journal of Oilseeds Research, 2020)
The objectives of the study to assess the yield performance and economics of linseed varieties under best agronomic management viz., weed, irrigation, nutrition and mechanization for high productivity and profitability in large scale technology and mechanization demonstrations at cultivators field of Sagar, Hoshangabad and Mandsaur district of Madhya Pradesh. Results revealed that the linseed crop is more profitable as compared to major rabi crops under limited water availability and sustainable use of natural resources and best possible agronomic management and mechanization.